1996
DOI: 10.1021/ja9540839
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Single Alkaline Phosphatase Molecules:  Reaction Rate and Activation Energy of a Reaction Catalyzed by a Single Molecule and the Effect of Thermal DenaturationThe Death of an Enzyme

Abstract: Single molecules of alkaline phosphatase are captured in a capillary filled with a fluorogenic substrate. During incubation, each enzyme molecule creates a pool of fluorescent product. After incubation, the product is swept through a high-sensitivity laser-induced fluorescence detector; the area of the peak provides a precise measure of the activity of each molecule. Three studies are performed on captured enzyme molecules. In the first study, replicate incubations are performed on the same molecule at constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
226
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(243 citation statements)
references
References 35 publications
15
226
1
1
Order By: Relevance
“…S2). Thus, in the present study, we could not detect intermolecular (static) variation as in other single molecule enzyme studies (14)(15)(16). Instead, the variability observed here is due to the limited number of events we could record from individual molecules.…”
Section: Two Dwell Time Populations Neither Resulted From Adp Accumulcontrasting
confidence: 62%
See 2 more Smart Citations
“…S2). Thus, in the present study, we could not detect intermolecular (static) variation as in other single molecule enzyme studies (14)(15)(16). Instead, the variability observed here is due to the limited number of events we could record from individual molecules.…”
Section: Two Dwell Time Populations Neither Resulted From Adp Accumulcontrasting
confidence: 62%
“…variation seen for other enzymes (14)(15)(16). Kinetic modeling suggested that the two dwell time populations originate from two active site conformers with different ATP binding features.…”
Section: Significancementioning
confidence: 87%
See 1 more Smart Citation
“…Further analysis using higher order correlation functions did not help discrimination between this simple model involving two alternative conformations and another involving a continuum of conformers. 195 This seminal study definitely confirmed the existence of static and dynamic heterogeneity in enzymes, 196,197 illustrating the power of single-molecule fluorescence studies for elucidating enzymatic reaction mechanisms inaccessible via ensemble methods.…”
Section: Quenching Due Tomentioning
confidence: 82%
“…The heterogeneity was found to be static on the hour timescale because the same enzyme molecule produces the same zone intensity after another incubation period. Using a similar approach, Craig et al studied single alkaline phosphatase molecules and found an even broader, multipeak distribution of activities (83). The heterogeneity was attributed to glycosylation and other posttranslational modifications, which produce nonidentical copies of enzyme in this system.…”
Section: Chemical Activitiesmentioning
confidence: 99%